1998
DOI: 10.1007/s002130050532
|View full text |Cite
|
Sign up to set email alerts
|

An amino acid mixture deficient in phenylalanine and tyrosine reduces cerebrospinal fluid catecholamine metabolites and alcohol consumption in vervet monkeys

Abstract: An amino acid mixture devoid of tryptophan, given orally, was previously shown to reduce cerebrospinal fluid levels of tryptophan and 5-hydroxyindoleacetic acid in vervet monkeys, as compared to a control mixture containing all essential amino acids. In the present study, we tested the possibility that a similar amino acid mixture containing tryptophan, but devoid of phenylalanine and tyrosine (the amino acid precursors of catecholamine neurotransmitters), would influence dopamine and noradrenaline metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…These depletion levels were similar in magnitude to those observed in previous studies using the TYR/PHE depletion method (plasma TYR/PHE: 53-76% depletion; TYR/PHE to LNAA ratio: 99% depletion) (Leyton et al, 1999(Leyton et al, , 2000Harmer et al, 2001). Previous studies in animals with TYR depletion between 30 and 40%, have shown significant reductions in catecholamine metabolites (Palmour et al, 1998) and catecholamine synthesis in the brain (Jaskiw and Bongiovanni, 2004;McTavish et al, 1999a). In humans, depletion of TYR/PHE to this magnitude has been shown to cause significant increases in plasma prolactin levels (an indirect measure of dopamine function) (Harmer et al, 2001;Harrison et al, 2004) and to impair dopamine dependent cognitive processes such as spatial working memory function (Harmer et al, 2001) due to reductions in 'tonic' dopamine.…”
Section: Discussionsupporting
confidence: 88%
“…These depletion levels were similar in magnitude to those observed in previous studies using the TYR/PHE depletion method (plasma TYR/PHE: 53-76% depletion; TYR/PHE to LNAA ratio: 99% depletion) (Leyton et al, 1999(Leyton et al, , 2000Harmer et al, 2001). Previous studies in animals with TYR depletion between 30 and 40%, have shown significant reductions in catecholamine metabolites (Palmour et al, 1998) and catecholamine synthesis in the brain (Jaskiw and Bongiovanni, 2004;McTavish et al, 1999a). In humans, depletion of TYR/PHE to this magnitude has been shown to cause significant increases in plasma prolactin levels (an indirect measure of dopamine function) (Harmer et al, 2001;Harrison et al, 2004) and to impair dopamine dependent cognitive processes such as spatial working memory function (Harmer et al, 2001) due to reductions in 'tonic' dopamine.…”
Section: Discussionsupporting
confidence: 88%
“…These depletion levels are equivalent to those observed using ATPD in previous studies (Harmer et al, 2001;Leyton et al, 2000). Furthermore, APTD studies with depletion levels of this magnitude have noted significant reductions in catecholamine metabolites (Palmour et al, 1998) and catecholamine synthesis (Jaskiw and Bongiovanni, 2004;McTavish et al, 1999a, b), and significant increases in plasma prolactin levels (an indirect measure of dopamine function) (Harmer et al, 2001). However, depletion of dopamine with ATPD in the present study resulted in no significant change in either PPI or P50 suppression.…”
Section: Dopamine Depletionsupporting
confidence: 81%
“…Second, although scans were scheduled at the nadir of plasma TyrPhe/LNAA ratio, when plasma prolactin concentrations (as a peripheral marker of reduced central DA function) previously elicited by this mixture were at their peak (Harmer et al, 2001), it is possible that the nadir of restricted central catecholamine synthesis occurred later (Palmour et al, 1998). Moreover, TPD decreases norepinephrine (NE) synthesis as well as DA synthesis (eg, Palmour et al, 1998). Therefore, activation changes cannot be definitively attributed to changes in DA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Large neutral amino acids (LNAAs) compete with Tyr for CNS uptake (Oldendorf, 1973) and stimulate hepatic protein synthesis to incorporate extant Tyr into proteins (Harper et al, 1970). This markedly lowers concentrations of Tyr in the plasma (Moja et al, 1996;Palmour et al, 1998) as well as catecholamine metabolites in the CSF (Palmour et al, 1998) and striatum (Biggio et al, 1976) within hours. Perturbations of Tyr/Phe availability have altered responses to DA-mediated pharmacological or environmental challenges (reviewed in Milner and Wurtman, 1986;Tam and Roth, 1997).…”
Section: Introductionmentioning
confidence: 99%